Amazing Things to Make and do for 7 Year Olds - Manley, Deborah (Kingfisher Books, 1994)
Bored and Fed up? Got Nothing to do? Then this is the book for you.Whatever your mood,you are bound to find something amazing to do.
Keywords: Juvenile literature- Non-Fiction